2011
DOI: 10.1007/s12262-011-0315-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting the Axillary Lymph Node Metastasis in Breast Cancer: Is Axillary Node Clearance Indicated in Every Breast Cancer Patient?

Abstract: The study was carried out to find out predictors of axillary lymph node metastasis in breast cancer and to evaluate its significance in selecting the group of patients in whom axillary dissection could be avoided. Ninety-five breast cancer patients who underwent mastectomy and axillary dissection were included in the study. Factors like patient's age, tumor size, histopathological type, histological grade and estrogen and progesterone receptor status were correlated with the axillary metastases. Out of 95 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
1
8
0
8
Order By: Relevance
“…The present study found significant correlation between high-grade breast cancers and node positive patients akin to the studies mentioned above. Hence, grading of breast cancer can be recommended to be used as an independent prognostic as well as predictive assessment tool, the findings in our study were statistically significant and similar to the findings of Chakraborty A et al, 14 Amrut V. Ashturkar et al 15…”
Section: Present Study In Comparison With Other Studiessupporting
confidence: 90%
“…The present study found significant correlation between high-grade breast cancers and node positive patients akin to the studies mentioned above. Hence, grading of breast cancer can be recommended to be used as an independent prognostic as well as predictive assessment tool, the findings in our study were statistically significant and similar to the findings of Chakraborty A et al, 14 Amrut V. Ashturkar et al 15…”
Section: Present Study In Comparison With Other Studiessupporting
confidence: 90%
“…6 In this study 742 patients had axillary lymph node metastasis. 8 In study by Gurleyik et al tumour size was not found to be an important factor for axillary involvement. Axillary metastasis was significantly associated with LVI (p<0.001).…”
Section: Review Of Literature Factors Affecting Involvement Of Axillamentioning
confidence: 87%
“…However, our study failed to show a significant relationship between combined ER & PR receptor status and LN involvement. However, a study by Ashturkar et al (3) showed that negative ER and PR status was significantly associated with low risk of axillary node metastasis.…”
Section: Receptor Status and Ln Involvementmentioning
confidence: 98%